2008
DOI: 10.1111/j.1083-6101.2008.01436.x
|View full text |Cite
|
Sign up to set email alerts
|

Connective collective action online: An examination of the hyperlink network structure of an NGO issue network

Abstract: Nonprofit, nongovernmental organization (NGO) hyperlink networks are connective public goods, or sets of interorganizational links that enable members and nonmembers to reach like-minded organizations in order to enhance the visibility of the network's goals. We extend collective action theory to account for both the level and structural signatures of contributions that generalist and specialist organizations make to these connective public goods. This study examines contributions that 48 English Speaking Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 43 publications
3
78
1
Order By: Relevance
“…TAPGs fall into the latter category. In organization studies , generalists have been found to play a broader role in interorganizational collective action (Barnett, Mischke, and Ocasio 2000;Shumate and Lipp 2008). The work of TAP Gs, again, parallels that of the transnational policy groups that lend cohesion to the global corporate elite.…”
Section: Discussionmentioning
confidence: 99%
“…TAPGs fall into the latter category. In organization studies , generalists have been found to play a broader role in interorganizational collective action (Barnett, Mischke, and Ocasio 2000;Shumate and Lipp 2008). The work of TAP Gs, again, parallels that of the transnational policy groups that lend cohesion to the global corporate elite.…”
Section: Discussionmentioning
confidence: 99%
“…A connection between two websites exists if a hyperlink existed between two websites and was present at least three times in a given year. Hyperlinks are useful for analysing the relationship that existed between media organizations; in cases where a hyperlink persists over time, prior research has established a connection between the presence of hyperlinks, and the presence of a relationship between organizations (Gao and Vaughn, 2006;Shumate and Lipp, 2008;Tsui, 2008;Turow and Tsui, 2008).…”
Section: And Then Came Social Mediamentioning
confidence: 99%
“…Hyperlink networks can be regarded as socio-communicational networks (Park and Thelwall 2008) and may show actual communication and information flows in social movements and interorganizational communication (Park and Thelwall 2003), demonstrate credibility and expertise (Park et al 2002), suggest collective action (Shumate and Lipp 2008), as well as discuss public agendas (Kim et al 2010).…”
Section: Hyperlink Network Analysismentioning
confidence: 99%